May Measurement Month 2019: an analysis of blood pressure screening results from Ghana-Sub-Saharan Africa. (20th May 2021) - Twumasi-Ankrah, Betty; Poulter, Neil R; Tannor, Elliot K; Adu-Boakye, Yaw; Nyarko, Obed O; Opoku, Gilder; Konadu, Saabea O; Aniagyei, Marian; Ogah, Anita; Baidoo, Timothy E; Mensah, Clarence; Clarke, Jonathan; et al.
Abstract: Raised blood pressure (BP) remains the biggest single risk factor contributing to the global burden of disease and to global mortality. Although a substantial number of people who have hypertension are either oblivious of it, not treated, or being managed but remain uncontrolled. May Measurement Month (MMM) is a global initiative led by the International Society of Hypertension (ISH) with the goal of increasing awareness of high BP and serving as a spur to establish screening programmes worldwide. An opportunistic cross-sectional survey of volunteers aged ≥18 years was carried out in May 2019. Measurement of BP and collection of relevant health information were performed according to a standardized protocol for MMM. Screening sites were set up in churches, mosques, health facilities, pharmacies, recreational parks, sports facilities, shopping centres, marketplaces, universities, workplaces, and community centres across four regions of Ghana. A total of 7102 participants gave their consent and were screened during MMM 2019. After multiple imputation, of all 7102 participants 1836 (25.9%) had hypertension. Of all 1836 participants with hypertension, 36.5% were aware of their status and 30.0% were on anti-hypertensive medication. Of 550 participants on antihypertensive medications, 46.1% had controlled BP (systolic BP <140 mmHg and diastolic BP <90 mmHg). Also, of all 1836 participants with hypertension, 13.8% had their BP controlled. Again, the proportion of participants with hypertension of those not receiving anti-hypertensive treatment was 1286 (19.6%). Data obtained from this project demonstrates that there is still a significant number of people with hypertension who are unaware of having it, are untreated, or are on treatment but remain uncontrolled. It also highlights the significance of BP screening campaigns as a tool to identify persons with elevated BP.